Biosensors Used in Dentistry: A Review - Nitish Kanta Mishra; Ramesh Nagarajappa; Debasruti Naik (Institute of Medico-legal Publications Pvt Ltd, 2021)
A bio-sensor is composed of six elements which include bio-receptor, transfusion element, chemically activeinterface, signal amplifier, signal processor and display. The analyze binds to the immobilized biologicalmaterial and forms a product. The product linked change is then converted by the transducer into electricsignals which can be amplified and measured. Oral fluid bio-sensors have the advantages of easy accessibilityand noninvasive sample collection, making them a novel method in disease diagnostics. However, itslimitations such as less sensitivity and specificity are overcome by the advent of new technologies such asmicrofluidics and nanofluidics. This review article discusses the concepts and applications of biosensors inthe field of dentistry.